The Novel in English Literature: "The Alchemist Novel as a Model" - Shilan Abdulrahman Abdulkarim (QALAAI ZANIST JOURNAL, 2024)
The research aimed to determine the degree of importance of using English language teaching websites in improving the speaking skill among secondary stage students from the teachers’ viewpoint. It also aimed at knowing the differences in this importance according to the variables of (gender, academic qualification, and number of years of experience). The research sample consisted of (125) male and female English language teachers in public secondary schools in Damascus Governorate, divided into (47) male teachers and (78) female teachers. A questionnaire prepared by the researcher was applied to those teachers after verifying its validity and reliability. The most important results of this research were the following: 1.There was a high level of importance for using English language teaching websites in improving the speaking skill among secondary stage students from the teachers’ viewpoint. 2.There were no statistically significant differences between teachers’ scores of their answers to the questionnaire of the importance of using English language teaching websites in improving the speaking skill among secondary stage students according to the variable of gender. 3.There were no statistically significant differences between teachers in the scores of their answers to the questionnaire of the importance of using English language teaching websites in improving the speaking skill among secondary stage students according to the variable of academic qualification. 4.There were no statistically significant differences between teachers in the scores of their answers to the questionnaire of the importance of using English language teaching websites in improving the speaking skill among secondary stage students according to the variable of years of experience.